Reação de leguminosas utilizadas em aléia a meloidogyne incognita e efeito de seus resíduos foliares sobre o patógeno - Nascimento, Fagner Sousa (2012)
This study aimed to evaluate the effect of the biomass of six legumes acácia (Acacia mangium), ingá (Inga edulis), gliricidia (Gliricidia sepium), leucena (Leucaena leucocephala), thrush (Mimosa caesalpiniaefolia) e o sombreiro (Clitoria fairchildiana) used in cultivation in alley crop added to soil in the form of mulch or biofumigation in the control of Meloidogyne incognita in okra and resistance these plants to nematodes. Biomass of legumes were applied to the soil, or incorporated in the form of 'mulch' or biofumigated with two incubation periods. The biomass of leucaena provided greater reduction in the index of galls and egg masses, then the sombrero. When applied in the form of 'mulch' waste of Leucaena sombreiro and inga were the most effective in reducing the nematode reproduction fator (FR). Waste, with the exception of Inga, when biofumigados, higher than the control in decreasing the incidence of galls and egg masses. Legumes differ in resistance to nematodes. Acacia mangio and gliricidia had reactions while susceptibility, Inga, Leucaena, thrush and sombrero were resistant. In alley cropping should avoid planting these species susceptible because they can serve as a source multiplier of the nematode